2018
DOI: 10.1103/physrevlett.121.228002
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking in Wrinkling Patterns: Gyri Are Universally Thicker than Sulci

Abstract: Wrinkling instabilities appear in soft materials when a flat elastic layer on an elastic substrate is sufficiently stressed that it buckles with a wavy pattern to minimize the energy of the system. This instability is known to play an important role in engineering, but it also appears in many biological systems. In these systems, the stresses responsible for the wrinkling instability are often created through differential growth of the two layers. Beyond the instability, the upper and lower sides of the elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 37 publications
4
45
0
Order By: Relevance
“…The gyral crowns are not affected as strongly due to their relatively small curvature (Bok, 1929). Our simulations are consistent with this principle, showing that an initially homogeneous cortex can develop cortical inhomogeneities through buckling, coherent with prior observations on homogeneous systems (Holland et al, 2018;Riccobelli and Bevilacqua, 2020;Welker, 1990).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The gyral crowns are not affected as strongly due to their relatively small curvature (Bok, 1929). Our simulations are consistent with this principle, showing that an initially homogeneous cortex can develop cortical inhomogeneities through buckling, coherent with prior observations on homogeneous systems (Holland et al, 2018;Riccobelli and Bevilacqua, 2020;Welker, 1990).…”
Section: Resultssupporting
confidence: 90%
“…Soft layered systems can be realized experimentally by gel slabs coated with gels with different properties (Auguste et al, 2014;. These systems have been used as simulacra for brain folding (Holland et al, 2018;Tallinen et al, 2016), where they were able to mimic the folding a 3D-printed human brain. Thus, the production of samples with sinusoidal variation of the top-layer thickness would allow for the experimental testing of our predictions.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it was shown that cortical folding approximately scales with surface area and thickness, and not with neuronal numbers ( Mota and Herculano-Houzel 2015 ). Additionally, through integration of imaging and mathematical modeling it was demonstrated that variations in cortical thickness within the cortex are caused by the physical forces emerging during the folding process ( Holland et al 2018 ). However, the problem of neocortex folding is a separate avenue of research, decoupled from the mechanisms that we want to investigate here.…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium value of ξ eq can be easily translated into a measured deflection through Eq. (11), which, at zeroth order in e/L, reads…”
Section: Initial Deflectionmentioning
confidence: 99%
“…Such activity is responsible for the appearance of a cleavage cytokinetic furrow driving the division of a single cell [2,3], or multicellular topological transitions during development such as mesoderm invagination in Drosophila [4,5] and inversion of the Volvox embryo [6], both involving hundreds of cells. The detailed patterns resulting from these mechanical interactions often involve instabilities where elastic stretching and bending deformations play an important role, such as in the rupture and subsequent curling of single red blood cells [7,8] or the formation of villi in the gut [9] and gyri and sulci in the brain [10][11][12] which shape entire organs.…”
Section: Introductionmentioning
confidence: 99%